Language as a Tool for Identifying Social Dissimilarity of Speakers - DraÃ§ini, Rrezarta (Richtmann Publishing, 2012)
â€œThe language is the only real means which serves to study the man and his behaviorâ€ [Rorty,1992]. It shows the most positive and the most wholesome element in which manâ€™s behavior finds its traces. â€œThere are no frontiers in manners among which people get connected with each-other for motifs of auto-identification, security, profit, religious belief. As a result, there are no frontiers in the amount and the varieties of linguistic communities that can be individualized in the societyâ€. [Bolinger,1975, p.15] Within the social community of a nation we distinguish even smaller groups of individual-speakers that have different linguistic features depending on various characteristics. The religious belief is one of the factors that influence on the identification of the linguistic differences. Such a fact becomes evident when there are speakers who belong to a nation, a state, a language, a dialect, even dwellers of the same city who are linguistically distinguished simply from the fact who belong to different religious beliefs. According to Hudsonâ€ the language performs a social function, either as a means of communication, or as a way of the social groupsâ€™ identification and their study, without referring to the society that uses it, which means excluding the possibility of finding social explanations about the used structuresâ€. [Hudson, 2002, p.15] Considering closely the impact that the religious differences have on language we have dwelled in Shkoder , a city in the north of Albania, where inhabitants of catholic and Muslim beliefs have lived for centuries. We have seen from close the linguistic situation in this city of about 120 thousand inhabitants. An inhabitant manages to identify an interlocutor whether this one belongs to his or her religious belief or not, since it carries with itself even linguistic differences depending on the religion to which he or she belongs. The institutional aspect of the religion deals with the conservatism in language. These religious-based linguistic differences are embedded in Albania although for 50 years, the communist dictatorship had legally banned the religious belief and had even killed a great number of clerics, even though for more than 70 years there have been marriages among youngsters of different religious beliefs, even though the subject â€“speakers belong to close social groups. Considering closely this linguistic reality in relation with the religious differences we have done a lot of interviews and observations.